Detection of lymph node metastases in esophageal cancer. Issue 4 (April 2011) - Sgourakis, George; Gockel, Ines; Lyros, Orestis; Hansen, Torsten; Mildenberger, Peter; Lang, Hauke
Lymph node status is the most important single prognostic factor in esophageal cancer. The detection of involved lymph nodes is therefore the key to cure. This article will provide a meta-analysis and metaregression analysis on the diagnostic performances of current lymph node-detection devices; discuss the recent status of the sentinel lymph node concept in esophageal cancer by the two sentinel node-mapping procedures (the radio-guided and the blue dye techniques) and the developing computed tomography (CT) lymphography; discuss the detection of micrometastases; and the potential clinical application of molecular-based patients'' profiles. Combined use of endoscopic ultrasonography fine-needle aspiration and CT significantly improves the diagnostic performance for regional lymph node metastases. Endoscopic ultrasonography is highly sensitive and specific for celiac lymph node metastases, while CT should mostly be performed in order to exclude other abdominal lymph node metastases. Sentinel lymph node navigation may be feasible for cT1N0 or cT2N0 esophageal cancer, and immunohistochemical staining of micrometastatic disease might be feasible in combination with this modality.